Comparison Study Influence The Third-Party Fund On Profitability With Bank Size As The Moderating Variable In Indonesia And Malaysia - Hermuningsih, Sri; Rahmawati, Anisya Dewi; Nasrulloh, Rifqi Syarif (Jurnal Manajemen Industri dan Logistik, 2022)
The objective of this research is to compare the correlation between third-party funds and profitability using bank size as a moderating variable of Islamic banking in Malaysia and Indonesia. The sample in this study used purposive sampling and obtained a sample of 10 Islamic banks in Malaysia, 10 Islamic banks Indonesia in 2016-2020. The data used is secondary data in the form of the annual reports or financial reports through the official website of each Islamic bank. To examine research data in the form of financial statements, this quantitative study used regression and moderate regression analysis. The results of the first analysis show that third-party funds from Indonesia and Malaysia Islamic banks show a significant effect on profitability (ROA), while the results of the second analysis show that third-party funds moderating the profitability of Indonesia and Malaysia Islamic banks.